Cerebrospinal Fluid and Microdialysis Cytokines in Severe Traumatic Brain Injury: A Scoping Systematic Review - Zeiler, Frederick A.; Thelin, Eric Peter; Czosnyka, Marek; Hutchinson, Peter J.; Menon, David K.; Helmy, Adel (Frontiers in Neurology, 2017)
Objective: To perform two scoping systematic reviews of the literature on cytokine measurement in: 1. Cerebral Microdialysis (CMD) and 2. Cerebrospinal Fluid (CSF) in severe traumatic brain injury (TBI) patients. Methods: Two separate systematic reviews were conducted: one for CMD cytokines and the second for CSF cytokines. Both were conducted in severe TBI patients only. Data Sources: Articles from MEDLINE, BIOSIS, EMBASE, Global Health, Scopus, Cochrane Library (inception to Oct 2016), reference lists of relevant articles, and gray literature were searched Study Selection: Two reviewers independently identified all manuscripts utilizing predefined inclusion/exclusion criteria. A two-tier filter of references was conducted. Data Extraction: Patient demographic and study data was extracted to tables. Results: There were 19 studies identified describing the analysis of cytokines via CMD in 267 severe TBI patients. Similarly, there were 32 studies identified describing the analysis of CSF cytokines in 1363 severe TBI patients. The two systematic reviews demonstrated: 1. Limited literature available on CMD cytokine measurement in severe TBI, with some preliminary data supporting feasibility of measurement and associations between cytokines and patient outcome. 2. Various CSF measured cytokines may be associated with patient outcome at 6 to 12 months, including: IL-1b, IL-1ra, IL-6, IL-8, IL-10 and TNF. 3. There is little to no literature in support of an association between CSF cytokines and neuro-physiologic or tissue outcomes. Conclusions: The evaluation of CMD and CSF cytokines is an emerging area of the literature in severe TBI. Further large prospective multi-center studies on cytokines in CMD and CSF need to be conducted.